PELUANG DAN TANTANGAN FINTECH (FINANCIAL TECHNOLOGY) SYARIAH DI INDONESIA - Hiyanti, Hida; Sukmadilaga, Citra; Fitrijanti, Tettet; Nugroho, Lucky (Moderation | Journal of Islamic Studies Review, 2022)
Currently, the development of Sharia Fintech (financial technology) in Indonesia is growing rapidly. But on the other hand, there are several phenomena and problems with conventional fintech that have a negative impact on society. Therefore, the existence of Sharia Fintech should be a solution to this phenomenon. The purpose of this research is to find out about the opportunities and challenges of Sharia Fintech (financial technology) in Indonesia. This study uses descriptive analysis with a qualitative approach. The data analysis technique used is an interactive model. The results of the study show that there are opportunities and challenges for Sharia Fintech in Indonesia, which consist of: regulations, human resources, technology, negative issues of Fintech and conventional capital